2014
DOI: 10.1007/s11095-014-1305-7
|View full text |Cite
|
Sign up to set email alerts
|

Substrate- and Dose-Dependent Drug Interactions with Grapefruit Juice Caused by Multiple Binding Sites on OATP2B1

Abstract: Substrate- and dose-dependent GFJ-drug interactions mediated by OATP2B1 might be explained in terms of the presence of MBS: interaction occurs only when drug and GFJ components share the same binding site on OATP2B1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 33 publications
4
51
1
Order By: Relevance
“…If this effect of GFJ could be attributed to inhibition of hepatic OATP-mediated transport, the plasma concentrations of both enantiomers would have been somewhat enhanced, as described previously [1e3]. In addition, recent studies have found that OATP2B1 is a major OATPtransporter in the small intestine and that the uptake/transport of fexofenadine in oocytes injected with OATP2B1 cRNA is significantly decreased in the presence of GFJ [15,33,34]. Therefore, these results suggested that GFJ inhibited the intestinal OATP2B1-mediated transport of fexofenadine enantiomers and may alter the pharmacokinetics of both enantiomers.…”
Section: Discussionmentioning
confidence: 63%
“…If this effect of GFJ could be attributed to inhibition of hepatic OATP-mediated transport, the plasma concentrations of both enantiomers would have been somewhat enhanced, as described previously [1e3]. In addition, recent studies have found that OATP2B1 is a major OATPtransporter in the small intestine and that the uptake/transport of fexofenadine in oocytes injected with OATP2B1 cRNA is significantly decreased in the presence of GFJ [15,33,34]. Therefore, these results suggested that GFJ inhibited the intestinal OATP2B1-mediated transport of fexofenadine enantiomers and may alter the pharmacokinetics of both enantiomers.…”
Section: Discussionmentioning
confidence: 63%
“…We and others have already demonstrated that SN-38 is a substrate of OATP1B1 (Nozawa et al, 2005) and OATP1B3 (Yamaguchi et al, 2008), which are clinically important liver-specific uptake transporters. Although OATP2B1 is also expressed in the liver (Tamai et al, 2000), OATP2B1 is likely to be pharmacologically more important in the intestine since OATP2B1, but not OATP1B1 or OATP1B3, is expressed in small-intestinal tissues (Tamai, 2012;Shirasaka et al, 2014). In our previous study, we failed to find a significant increase of SN-38 uptake by OATP2B1-expressing Xenopus oocytes (Nozawa et al, 2005).…”
Section: Discussionmentioning
confidence: 72%
“…It was reported that the plasma concentration of fexofenadine after oral administration was decreased by coingestion with fruit juices, presumably owing to inhibition of intestinal uptake (Dresser et al, 2002). We suggested a significant contribution of OATP2B1 to intestinal absorption of fexofenadine and proposed that this transporter is a site of interaction with fruit juice components (Imanaga et al, 2011;Shirasaka et al, 2013Shirasaka et al, , 2014. OATP1B1 and 1B3 have broad substrate selectivity and mediate hepatic uptake of various drugs (Shitara et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…As OATP2B1 has two activity sites with different substrate affinity profiles, it has been shown that the function of each site can be independently evaluated using different substrate concentrations [19,20]. Based on this information, the E 1 S (Sigma, St Louis, MO) concentration was set to 5 nM for Hsite-mediated uptake and to 50 M for L-site-mediated uptake.…”
Section: Transport Assay For Validation Of Oatp2b1 Expression In Hek2mentioning
confidence: 99%
“…For example, it has been shown that there are at least two sites which show different affinity to estrone sulfate (E 1 S, a classical OATP2B1 substrate), which are designated as the high or low E 1 S affinity site (H-site or L-site), respectively [19], and it appears that these sites are interchangeable in a substrate-dependent manner (e.g. the H-site for E 1 S uptake can be the L-site for another drug) [20]. Furthermore, OATP2B1 inhibitors have been shown to exhibit interaction preferences related to those sites, as exemplified by taurocholic acid (TCA) and testosterone (TST) as selective inhibitors of the H-and L-sites for E 1 S uptake, respectively [19].…”
Section: Introductionmentioning
confidence: 99%